Toltrazuril-Loaded Polymeric Nanocapsules as a Promising Approach for the Preventive Control of Coccidiosis in Poultry - Lana Flávia Baron; Francisco Noé da Fonseca; Shaiana Salete Maciag; Franciana Aparecida Volpato Bellaver; Adriana Mércia Guaratini Ibeli; Marcos Antônio Zanella Mores; Gabryelle Furtado de Almeida; Silvia Stanisçuaski Guterres; Ana Paula Almeida Bastos; Karina Paese (MDPI AG, 2022)
Coccidiosis is a disease caused by intracellular protozoan parasites of the genus Eimeria that affect the intestinal tract of poultry. However, strain resistance and drug residue in the carcass have drawn the attention of the productive sector. The nanotechnology can improve the biological effect of drugs, reducing of administered doses and toxic effects. Due to this, toltrazuril-load polymeric nanoparticles based on Eudragit® S100 (NCt) or poly-ε-caprolactone (LNCt) were developed to prevent coccidiosis in broilers. Nanoformulations were produced and showed homogeneous particle diameter distribution in the nanometer range (z-average and D (4.3) < 200 nm), negative zeta potential (<−8.93 mV), drug content ~100%, and encapsulation efficiency >90%. Cell viability assays using avian fibroblasts showed that LNCt presented no relevant toxicity up to 72 h. LNCt was then prophylactically administrated to chicken followed by challenge with Eimeria oocysts. The evaluation of the small intestine and cecum showed that the treatment with LNCt (3.5 mg/kg/day) in drinking water reduced the lesion scores and oocysts excretion, similar to the reference medicine containing toltrazuril (Baycox®, 7 mg/kg/day). The current study shows the potential protective use of nanoencapsulating anticoccidial drugs as a promising approach for the control of coccidiosis in poultry.